PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF KIBUDI BOOKS PADA BIDANG SEJARAH KEBUDAYAAN ISLAM DI SEKOLAH DASAR - Pitri Lestari; Iis Irma Lisnawati; Sri Ana; Ani Nur Aeni (Journal of Research and Thought on Islamic Education (JRTIE), 2022)
Learning using interactive learning media aims to facilitate the learning process and foster teacher creativity and innovation in designing the learning process. Therefore, this research intends to develop a learning product in the form of interactive digital ebooks. The formulation of the problem in this study are: 1) What is the description of general learning media in the field of SKI in class IV? 2) How is the design of the Kibudi Book as an interactive digital learning media in the field of SKI in grade IV? 3) How are the results of the validity test regarding the Kibudi Books product as an interactive digital learning medium in the field of SKI in grade IV?. The model used is DD (design and development). The data obtained in the form of quantitative and qualitative by using two methods of data collection, namely observation and questionnaires. The results of the study show 1) Learning about SKI material in general only uses the lecture method with book media 2) The design of this digital interactive learning media includes three stages, namely; (a) needs analysis, (b) design, (c) development and implementation, 3) The results of the validity test regarding kibudi products include: (a) the results of a design and material expert review with very valid qualifications (100%). (b) the results of user reviews of teachers with very valid qualifications (85.71%), (c) results of user reviews of users with qualifications (97.05%) with very valid qualifications. So it can be used that the development of interactive digital learning media Kibudi Book is feasible in the learning process. Keywords: Learning Media, Isra Miraj, Kibudi Books.